2017
DOI: 10.1037/fsh0000232
|View full text |Cite
|
Sign up to set email alerts
|

Couples coping with cardiovascular disease: A systematic review.

Abstract: Principal implications of this review's findings relate to our fields' need to provide more care focused on dyads (vs. individual patients), adopt an integrated model in health care, and conduct systemic, longitudinal research to gain a better grasp on how coping changes over time. Doing so will serve to better equip providers in the support of patients and partners living with CVD. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…Although it is unnecessary to distinguish good coping from bad coping (Lazarus ), the accessibility of coping resources shape the ways that patients manage their chronic conditions, then possibly affect their health outcomes (Löffler et al . ; Trump & Mendenhall ; Yorgason et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is unnecessary to distinguish good coping from bad coping (Lazarus ), the accessibility of coping resources shape the ways that patients manage their chronic conditions, then possibly affect their health outcomes (Löffler et al . ; Trump & Mendenhall ; Yorgason et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, disability is an interpersonal experience in close relationships. This has repeatedly been found in other chronic health conditions such as cancer (Hagedoorn et al, 2008), diabetes (Lister et al, 2013), and cardiovascular disease (Trump and Mendenhall, 2017). The review also indicated that dyadic challenges were largely comparable across health impairments.…”
Section: Discussionmentioning
confidence: 54%
“…According to the findings, young patients (≤40 years old) may be more at risk of isolation after the implant of an ICD (Dubin et al, 1996 ; Sears et al, 2009 ; Larimer et al, 2016 ). This leads us to underline the importance of developing research among patients and their relatives, especially couples, to improve their emotional and physical outcomes (Sher et al, 2014 ; Varela Montero and Barrón López de Roda, 2016 ; Lyons et al, 2017 ; Trump and Mendenhall, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also include a focus on post-traumatic stress disorder as, despite the vast literature pointing out its prevalence among cardiac patients (Vilchinsky et al, 2017 ), it was not addressed in the included studies. Research could also include caregivers as they were found to be impacted by the disease (Trump and Mendenhall, 2017 ); thus, they may influence both the well-being and the adherence of patients (Sher et al, 2014 ; Varela Montero and Barrón López de Roda, 2016 ; Lyons et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%